2009
DOI: 10.19173/irrodl.v10i2.593
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Well-Being of Israeli Students and Attitudes toward Open and Distance Learning

Abstract: This article reports on a study conducted in Israel at an academic institution. The study investigates the correlation between students’ attitudes toward open and distance learning (ODL) and their perceived self-esteem and loneliness at the last stage of their online learning experience. For this study, 120 students were asked to complete a questionnaire. The students were enrolled in three fully online academic courses, which were similar in their instructional design approach although different in content. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
(10 reference statements)
1
9
1
Order By: Relevance
“…Online students also showed a significant relationship between selfacceptance and perceived wellness, differing from that found with traditional students. Positive correlations between self-esteem, including high degrees of self-awareness in online students was also found by Kurtz et al, (2009). The significant relationship found between purpose in life, and perceived wellness corroborates findings by Adams et al, (2000).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Online students also showed a significant relationship between selfacceptance and perceived wellness, differing from that found with traditional students. Positive correlations between self-esteem, including high degrees of self-awareness in online students was also found by Kurtz et al, (2009). The significant relationship found between purpose in life, and perceived wellness corroborates findings by Adams et al, (2000).…”
Section: Discussionsupporting
confidence: 77%
“…Students who participate in an online learning environment, according to Scheer and Lockee (2003), often express a need for access to wellness resources. In a separate study, Kurtz, Amichai-Hamburger, and Kantor (2009) found positive correlations between selfesteem and students' attitudes about online learning, including high degrees of self-awareness. In the online environment, the students' desire for self-awareness is inhibited by the difficulty to develop social relationships due to geographic distances.…”
mentioning
confidence: 85%
“…Environments that students perceive as positive tend to lead to improved student achievement and attitudes (Chang & Fisher, 2001). Research involving learning environments has a tradition of considering the association between perceptions of psycho-social characteristics of the environment and of students' cognitive and affective outcomes (For example, Kurtz, Amichai-Humburger, & Kantor, 2009). Learning environments research has demonstrated that across languages, nations, cultures, subject matter, and educational levels, there are consistent associations between environmental perception and student outcomes (Fraser, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Students report feelings of loneliness and social detachment when learning online because the physical reinforcement of the F2F learning environment is lacking. These feelings have a negative effect on their learning achievements (Lazenby, 2003;Coates, 2006;Bates & Khasawneh, 2007;Kurtz & Amichai-Hamburger, 2008). In most of these reports, learners express the need to bridge the gap with their online instructor and peers.…”
Section: Lonelinessmentioning
confidence: 99%